2020
DOI: 10.1177/1940082920961491
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Regulation and Development Transformation in the Tropical and Subtropical Cities of China: A Big Data Analysis

Abstract: This paper studies the effects of Key Control Areas (KCA) policy implemented by the Chinese government in 2012 on city development transformation, in which strict environmental regulations were imposed in KCA cities in both tropical and subtropical zone. Based on the panel data of 155 tropical and subtropical cities in China from 2000 to 2017, we use a simple Differences-in-Differences approach to estimate the effects. Results show that more draconian environmental regulation has significant positive effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Consequently, enterprises' inappropriate production behavior has been regulated and restricted [43]. In addition, this has promoted the internalization of the social cost of environmental pollution emissions [44], guided the flow and distribution of resources among industries, and transformed industrial development from resource-driven to technologicaldriven, thereby promoting industrial structure transformation [45]. Moreover, strict environmental regulations may encourage enterprises to adapt their product and management structures, improve their independent innovation capacity, and create societal excitement for innovation, resulting in industrial structure transformation [17,23].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, enterprises' inappropriate production behavior has been regulated and restricted [43]. In addition, this has promoted the internalization of the social cost of environmental pollution emissions [44], guided the flow and distribution of resources among industries, and transformed industrial development from resource-driven to technologicaldriven, thereby promoting industrial structure transformation [45]. Moreover, strict environmental regulations may encourage enterprises to adapt their product and management structures, improve their independent innovation capacity, and create societal excitement for innovation, resulting in industrial structure transformation [17,23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yasmeen et al [3] found that severe environmental regulations, rather than voluntary environmental rules, negatively influenced ecological efficiency in places with low resource reliance. Deng et al [44] indicated that ER influenced the transformation of cities with a large population and high pollution levels. Similarly, ER can promote industrial transformation in cities with high and low economic development but may not affect cities with medium economic growth.…”
Section: Effect Of Environmental Regulation On Industrial Transformationmentioning
confidence: 99%
“…Strict but reasonable environmental regulatory policies, such as Pigovian taxes and pollution permits, can encourage producers to internalize external uneconomic behavior, encourage producers to actively participate in green innovation research and development activities, increase green product output, and generate "innovation compensation" effect to offset the impact of compliance costs (Porter and Vander, 1995). Later, many scholars conducted a series of explorations around Porter's hypothesis and believed that the greater the intensity of environmental regulation, the more conducive to driving the development of regional green innovation levels, and there is a positive linear correlation (Rubashkina, 2015;Santis, 2017;Tang et al, 2019;Deng et al, 2020). So, does environmental regulation have a significant positive or negative impact on green innovation?…”
Section: Introductionmentioning
confidence: 99%
“…,Gholizadeh et al (2020),Bifulco et al (2021),Yu et al (2021b),Jiang et al (2021b),,Ma et al (2021a),Li and Mao (2020),Deng et al (2020),Bertsimas and Kallus (2020),Goodarzian et al (2021),Chakraborty and Das (2021),Ali et al. (2021a),Moghimi and Beheshtinia (2021),Dai and Liu (2020),Li et al (2020c),Abdella et al (2020),Wong et al (2021),Kuo et al (2021), Narwane et al (2021,Zhou and Guo (2021),Salamai et al (2021), Park (2021),Wu et al (2022),Asghari et al (2021),Fang and Su (2021),Gumte et al (2021), Yeboah-Ofori et al (2021,Wan (2021), Ping, Huang (2021), Guillermo Muñoz et al (2020),Lunardi and Lima Junior (2021),Xiang (2020),Khan et al (2020),Sang (2021), Jianying et al ( 2021), Abdelsamad et al (2021), Nezamoddini et al (2020), Abdelaziz et al (2020), Yang et al (2021d), Akbarian-Saravi et al (2020), Chen et al (2021a) Logistics Intelligent transportation system Dimokas et al (2020), Ibrahim et al (2020), Chen et al (2021b), Hwang (2021), Lorenc et al (2021), Wiegmans et al (2020), Mouammine et al(2020), Zanin et al (2020), Cerquitelli et al (2020), TASHEV et al (2020), Zhang et al (2020b), Kinra et al (2020), George and Santra (2020), Gupta et al (2020), Chen (2020), Ding (2020), Kosowska-Stamirowska (2020), Harrison et al (2020), Chen et al (2021c), Han et al (2021a), Sarabia-Jácome et al (2019), Lock et al (2021), Tsolakis et al (2021), Jurdana et al (2020), Oucheikh et al (2021), Lee and Jeong (2021), Adi et al (2020), Ren et al (2020), Nadi et al (2021) In-transit inventory management Li et al (2020b), Sun et al (2020b), Yi and Ma (2020), Li and He (2021), Kim et al (2020a), Molaris et al (2021) Logistics planning Moscoso-López et al (2021), Balster et al (2020), Liang and Wang (2021), Mangina et al (2020), Cheng and Pan (2021), Choi (2020), Yue et al (2021), Monteil et al (2021), Vorkapić et al (2021), Hathikal et al (2020), Wang and Y...…”
mentioning
confidence: 99%